Itraconazole for invasive fungal infection with pediatric malignancies - Kobayashi, Ryoji; Suzuki, Daisuke; Yasuda, Kazue; Kobayashi, Kunihiko (Pediatrics international, 2010)
Background:  Invasive fungal infection (IFI) is an increasingly common and often fatal infection in children with hematological malignancies and solid tumor. Prophylactic therapy with anti‐fungal agents is very important for these patients, because the early diagnosis of IFI is very difficult. Procedure:  A total of 0.5 mL/kg per day of itraconazole oral solution (ITCZ‐OS) was administered in twice‐daily doses to 22 children with hematological malignancies who had received chemotherapy, and its usefulness and safety regarding the prevention of IFI were examined. Result:  Prophylactic therapy with ITCZ‐OS was completed in 18 (81.8%) of the 22 children. Of these, IFI was not strongly suspected in any child. Side‐effects included non‐alcoholic steatohepatitis in two children, syndrome of inappropriate anti‐diuretic hormone secretion in one, and liver dysfunction in one. The administration of ITCZ‐OS was discontinued in these cases. These four children had received vincristine sulfate (VCR) or irinotecan hydrochloride, which were reported to interact with ITCZ. In most children the plasma levels of ITCZ were satisfactory. The plasma levels, however, were slightly increased in VCR‐treated children; ITCZ should be carefully administered. Conclusion:  Although the number of subjects was small in the present study, the plasma concentrations of ITCZ‐OS favorably increased in the children with hematological malignancies, suggesting that this agent exhibits prophylactic effects on IFI. It must be considered, however, that some combined agents cause side‐effects via their interactions with ITCZ.